NILAI POSTMODERNISME DALAM KOMUNIKASI DAN VISUAL KAMPANYE DIGITAL KONTEN KESADARAN PUBLIK BCA 'DON’T KNOW? KASIH NO!' - Razali, Geofakta; Novianti, Suci Marini; Kristanti, Desi Dwi; Budiharjo, Slamet (Jurnal Komunikasi & Media Digital, 2024)
This study evaluates the representation of postmodernist values in Bank Central Asia's (BCA) "Don’t Know? Kasih No!" campaign, which aims to strengthen public awareness regarding online fraud. Employing a quantitative content analysis method based on Holsti's formula, the research quantifies and analyzes the frequency of audio-visual elements within YouTube videos, encompassing dialogue, music, and transitions. In parallel, the campaign's posters are deconstructed using Roland Barthes's semiotic. Findings indicate a consistent and recurrent audio-visual narrative strategy that directs towards preventive actions against online fraud, while the semiotic analysis of posters reveals how design elements strategically create myths that endorse a critical and prudent stance within an urban environment. Overall, the campaign reflects BCA’s success in implementing postmodernist principles and highlighting the significant role of dynamic and contemporary visual communication in the digital era.